Orthophosphoric Acid Activated Ananas comosus Leaves Carbon as an Adsorbent for the Removal of Basic Yellow 2 - Parimalam, R.; Raj, V.; Sivakumar, P. (Asian Journal of Chemistry, 2012)
Removal of basic yellow 2 from aqueous solution by adsorbing it on an activated carbon prepared from Ananas comosus (L) leaves was investigated by batch method. The studies were conducted by varying the pH, initial dye concentration, contact time and temperature. The sorption data was analyzed using the Langmuir, Freundlich, Tempkin isotherm and Dubinin-Radushkevich (D-R) isotherm models. The maximum monolayer adsorption capacity was found to be 227.27 mg/g. The Freundlich model is more appropriate to explain the adsorption phenomena with good fit. The data were also analyzed in terms of their kinetic behaviour and was found to obey the pseudo second order equation with an r2 value of 0.999.